Hemorrhages in Polycythemia Vera and Essential Thrombocythemia: Epidemiology, Description, and Risk Factors—Learnings from a Large Cohort - Nicol, Christophe; Ajzenberg, Nadine; Lacut, Karine; Couturaud, Francis; Lippert, Eric; Pan-Petesch, Brigitte; Ianotto, Jean-Christophe (Thrombosis and Haemostasis, 2022)
Background The management of myeloproliferative neoplasms (MPNs) is based on the reduction of thrombotic risk. The incidence, impact, and risk factors of bleedings have been less studied.Methods All patients with polycythemia vera (n=339) or essential thrombocythemia (n=528) treated in our center are included in OBENE (Observatoire BrEstois des NEoplasies myéloprolifératives) cohort (NCT02897297). Major bleeding (MB) and clinically relevant nonmajor bleeding (CRNMB) occurring after diagnosis were included, except after leukemic transformation.Results With a median follow-up of 8.3 years, incidence of hemorrhages was 1.85% patient/year, with an incidence of MB of 0.95% patient/year. The 10-year bleeding-free survival was 89%. The most frequent locations were digestive tract, “mouth, nose and throat,” and muscular hematoma. The case fatality rate of MB was 25%. The proportion of potentially avoidable postoperative bleeding was remarkable (17.6%). In multivariable analysis, eight risk factors of bleeding were identified: leukocytes >20 G/L at diagnosis (hazard ratio [HR]=5.13, 95% confidence interval [CI]: 1.77–14.86), secondary hemopathies (HR=2.99, 95% CI: 1.27–7.04), aspirin use at diagnosis (HR=2.11, 95% CI: 1.24–3.6), platelet count >1,000 G/L at diagnosis (HR=1.93, 95% CI: 1.11–3.36), history of hemorrhage (HR=1.82, 95% CI: 1.03–3.24), secondary cancers (HR=1.71, 95% CI: 1.01–2.89), atrial fibrillation (HR=1.66, 95% CI: 1.01–2.72), and male sex (HR=1.54, 95% CI: 1.02–2.33). The occurrence of a CRNMB increased the risk of a secondary MB (odds ratio=6.13, 95% CI: 2.86–12.6, p<0.00001). Most patients taking hydroxyurea displayed a nonmacrocytic median corpuscular value in the months preceding bleeding (51.4%).Discussion The morbidity and mortality of bleedings in MPN should not be underestimated, and patients with platelet count >1,000 G/L and/or leukocytes >20 G/L, and possibly patients who suffered from a CRNMB could benefit from cytoreduction to reducing bleeding risk. Postoperative bleedings represent a substantial proportion of bleeding and could be better prevented.
Keywords: hemorrhage; polycythemia vera; essential thrombocythemia; risk factors